Digital Humanities Review: Livingstone Online (Historia, 2021)
Livingstone Online is an open-access internet resource and publishing project hosted by University of Maryland Libraries in the USA. The aim of the website is to make available online all the letters, journals, diaries, books, notebooks and knownmiscellaneous items which originated from David Livingstone’s pen. The project collaborates with leading British and international archives, libraries and educational institutions and is also responsible for the Livingstone Spectral Imaging Project which is a collaborative, international effort to use spectral imaging technology and digital publishing to make available a series of formerly illegible diaries and letters produced when Livingstone, during his last years, was stranded without ink or writing paper in central Africa (http://livingstoneonline.org/spectral-imaging).
Keywords: Livingstone Online; Digital Humanities Review